EFEKTIVITAS MEDIA KOMIK BERNUANSA CTL UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Nela Sari Yolanda; Andi Kurnia Riski Sanneng (LPPM Universitas Ekasakti, 2024)
The lack of student interest in learning mathematics is caused by the teaching materials used not being able to make students active so that student scores have not reached the Minimum Completeness Criteria (KKM). School teaching materials contain many questions with almost the same level of difficulty and solution methods so that students get a little bored of doing them. So it is necessary to develop mathematics learning media that can improve students' mathematics learning outcomes. In this research, mathematics learning media was developed in the form of comics with Contextual Teaching and Learning (CTL) nuances. In this development, it is hoped that effective mathematics learning media results will be obtained. The research subjects were students of class VII C at SMP N 20 Jambi City as the experimental class and class VII B as the control class. This learning tool has been effective as seen from the average student learning outcomes. It can be seen from the learning results of the experimental class that 90% of students have achieved a score above the KKM, while the learning results from the control class have 70% of students achieving a score above the KKM. Based on these results, it can be concluded that comic learning media with CTL nuances for improving the learning outcomes of class VII C students can be declared effective.